Determinants of Wheat Production in Libya - Faraj, Fouzi Salih; Farhana, Ismail; Rossazana, Ab Rahim (Human Resource Management Academic Research Society (HRMARS), 2020)
Agriculture has an important place in Libyan economy since it is a major source and necessary to maintain this sector to ensure food and food security. The purpose of this study is to examine the effect of the cultivated of wheat, rainfall and temperature range on wheat production. Time-series data were employed and analysed by using the ARDL bounds test approach of cointegration. The results of estimated coefficients in long run relationship indicate that cultivated of wheat has a positive effect on wheat production and highly significant influence at 1% probability level. Likewise, rainfall is found to be a positive sign related to wheat production but not significant. Meanwhile, the effect of temperature is negatively associated with wheat and non-significant at probability levels.